Reviews and notices - Tom Lundskær-Nielsen; David Isitt; Jeremy Lane; Alistair Davies; Bertil Nolin; Alvar Ellegård; Maria Holmgren Troy; Elleke Boehmer; Gunnar Bergh; Patrick Burke; Göran Kjellmer; Helena Bergmann; et al. (Moderna Språk)
Includes the following reviews: